Basil (Ocimum Basilicum L.) as a Natural Antioxidant. Issue 1 (22nd July 2012) - Veronezi, Carolina Médici; Costa, Tainara; Jorge, Neuza
Abstract The antioxidant activity from basil ethanol extract, the effect on oxidative stability, total polar compounds, tocopherols levels and fatty acid profile in soybean oil under thermoxidation were evaluated. The basil leaves were dried in lyophilizer, ground and subjected to extraction with ethanol. The soybean oil (SO), soybean oil with 50 mg/kg of tert‐butylhydroquinone (TBHQ), soybean oil with 3, 000 mg/kg of extract (BE) and soybean oil with 3, 000 mg/kg of extract and 50 mg/kg of TBHQ (mixture) treatments were subjected to 180 ± 5C for 20 h. Oil samples were taken at 0, 10 and 20 h and subjected to analysis. The addition of the basil extract increased oxidative stability and resulted in lower formation of total polar compounds. Although the content of tocopherols and polyunsaturated fatty acids decreased over the course of heating, their values remained higher than the SO treatments. Synergistic effect was not observed in the mixture treatment. Practical Applications Antioxidants are important ingredients in food processing because they have the capacity to protect foods containing oils and fats, from damage caused by free radicals and reactive oxygen species. Synthetic antioxidants are widely used in the food industry; however, their utilization has been questioned due to toxicity. Therefore, there is a growing interest in the use of natural antioxidants to reduce or replace the synthetic antioxidants. Several species of the Lamiaceae family are used in cooking, medicine and by the pharmaceutical industry, standing out is basil. Being rich in compounds with high antioxidant activity, basil extract can be used to replace synthetic antioxidants used in vegetable oils.